An Analysis of English Diphthong Pronunciation by the Students of the English Education Study Program - Sefran Ponidi; Syafrizal Sabarudin; Arasuli Arasuli (Journal of English Education and Teaching, 2021)
This research wasaimed to know howEnglish students in Universityof Bengkulu, EnglishEducationStudy ProgrampronouncedEnglish Diphthongs.Thisresearchuseddescriptive qualitativemethod. The population in this research was the 79 sixth semester students of English EducationStudy Program. The numbers of samples were 20% of the population. The Students were asked to pronounce 8 diphthongs in English. The research was doing input the audio from native speaker and data recordedby each student into Audacity. Then, comparing both of the data.The research was usingAudacity as the technology to analyze and to see the pattern of the data recorded in order to check the correct and incorrect of the students’ pronunciation. The data of the research consisted of 8 diphthongs and each diphthong consisted of 3 words including in the word diphthongs. The total words in this study were 24 words. The resultof thisresearchshowedthatmostofEnglishstudentspronouncedEnglish diphthongs[e?], [o?], [a?], [??], [??] and [??] incorrectly.Itshowed thatthestudents stilldid not know about English diphthongs. Meanwhile,thestudentsweregoodatpronouncingdiphthongs suchas[a?]and [??] with more than 58% of correct pronunciation.